The Interplay between Traumatic Brain Injury, Cocaine Abuse, and Genetic Mutations in the Development of Parkinsons Disease: A Review - Qutboddin, Mohamad; Ahmed, Syed Sagheer; Abbas, Nahid; Ali, Mohammad; Raghunathanaidu, Bharathi Doddla (Indian Journal of Pharmaceutical Education and Research, 2026)
Parkinson's Disease (PD) is a neurodegenerative disorder characterized by the depletion of dopamine neurotransmitters and receptors. Although the etiology of PD is multifactorial, emerging evidence suggests that Traumatic Brain Injury (TBI), cocaine abuse, and genetic mutations may contribute to the development and progression of PD. This review summarizes the current understanding of the interplay between TBI, cocaine abuse, and genetic mutations in DA homeostasis in PD. Here, we discuss the molecular mechanisms underlying DA depletion and receptor dysfunction in PD, and how TBI, cocaine abuse, and genetic mutations may exacerbate these processes. Ultimately, a complex relationship between TBI, cocaine abuse, genetic mutations in dopamine, and PD has been identified.
Keywords: Cocaine abuse; Dopamine; Genetic mutation; Parkinson's disease; Traumatic brain; injury